PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MEDIA GAMBAR PERISTIWA PADA SISWA KELAS SMK YPK PURWAKARTA - M Lukman Leksono Lukman; Riyatno (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study aims to improve poetry writing skills in Grade X students of SMK YPK Purwakarta through the use of event image media. The primary problem underlying this research was the students' low ability to find ideas, determine themes, and choose appropriate diction, as evidenced by an initial average score of 64.2 (below the minimum mastery criteria/KKM). The method used was Classroom Action Research (CAR) conducted in two cycles, encompassing planning, action, observation, and reflection phases. The results showed a significant improvement in each cycle. In Cycle I, the students' average score increased to 73 with a success rate of 63%. In Cycle II, the average score rose sharply to 86.43 with a success rate reaching 97%. Based on these results, it can be concluded that the use of event image media is effective in improving the quality of both the process and results of poetry writing instruction, as well as enhancing student activity and motivation in the classroom. Keywords: Writing Skills, Poetry, Event Image Media, Classroom Action Research.